2008
DOI: 10.1016/j.drup.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of mTOR in anticancer drug resistance: Perspectives for improved drug treatment

Abstract: The mammalian target of rapamycin (mTOR) pathway plays a central role in regulating protein synthesis, ribosomal protein translation, and cap-dependent translation. Deregulations in mTOR signaling are frequently associated with tumorigenesis, angiogenesis, tumor growth and metastasis. This review highlights the role of the mTOR in anticancer drug resistance. We discuss the network of signaling pathways in which the mTOR kinase is involved, including the structure and activation of the mTOR complex and the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
187
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(199 citation statements)
references
References 157 publications
(171 reference statements)
5
187
0
7
Order By: Relevance
“…Mutations in it are almost exclusively gain-of-function 50 and have been identified in about 12% of all human cancers. 51 They have specifically been found in breast, cervical, ovarian, gastric, colorectal, and lung, 20 and in up to 27% of UCCs. 49 A study evaluating renal and collecting system diseases found that PIK3CA mutations were specific to UCC of the renal pelvis as compared with other renal neoplasms such as renal cell carcinoma.…”
Section: Pi3k Mutations Characterize a Subset Of Bladder Cancersmentioning
confidence: 99%
See 3 more Smart Citations
“…Mutations in it are almost exclusively gain-of-function 50 and have been identified in about 12% of all human cancers. 51 They have specifically been found in breast, cervical, ovarian, gastric, colorectal, and lung, 20 and in up to 27% of UCCs. 49 A study evaluating renal and collecting system diseases found that PIK3CA mutations were specific to UCC of the renal pelvis as compared with other renal neoplasms such as renal cell carcinoma.…”
Section: Pi3k Mutations Characterize a Subset Of Bladder Cancersmentioning
confidence: 99%
“…14,20 It regulates actin cytoskeleton remodeling, whereas mTORC1 is primarily responsible for nutrient and growth factor signal sensing. 14,[20][21][22] mTOR PATHWAY ACTIVATION mTOR is only one part of the larger phosphatidylinositol 3 kinase (PI3K)/Akt/mTOR pathway ( Figure 1). Upstream activation of this pathway begins when growth factors (insulin, insulin-like growth factor, platelet-derived growth factor), mitogens, hormones, or nutrients activate PI3K.…”
Section: Mtor and Its Role In Cellular Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies suggest that these proteins are commonly activated in cancer cells, contributing to cell proliferation and carcinogenesis (Dancey and Sausville 2003, Dillon et al 2007, Jiang and Liu 2008.…”
Section: The Pi3k/akt/mtor Pathwaymentioning
confidence: 99%